2021
DOI: 10.4103/jcd.jcd_126_21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proanthocyanidin and riboflavin on shear bond strength of a nanocomposite to deep dentin – An in vitro Study

Abstract: Aims: The objective of this study was to evaluate the effect of two collagen crosslinking agents on shear bond strength of a nanocomposite using total-etch adhesive to deep dentin. Materials and Methods: Thirty maxillary central incisors were selected for the study and each tooth was divided into two equal halves with diamond disc (n = 60). Proximal surfaces were prepared to expose the deep dentin until the remaining dentin thickness was approximately 1 mm. The specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In 2018, Gré et al confirmed that strong bonds can be formed between the amide carbonyl group of collagens and the phenolic hydroxyl group of proanthocyanidins, leading to the formation of the proline–proanthocyanidin complex [ 65 ]. Next, in 2021, a report suggested that the biomodification of deep dentin with proanthocyanidins showed the highest shear BS, followed by riboflavin and the control group (no collagen crosslinker modification) [ 157 ]. Proanthocyanidins can be incorporated into the etching solution and experimental primer to enhance the stability of bonding, while proanthocyanidins incorporated into an experimental adhesive showed no negative effect but stabilized the interfacial resin–dentin bonds, confirming the outcome obtained in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Gré et al confirmed that strong bonds can be formed between the amide carbonyl group of collagens and the phenolic hydroxyl group of proanthocyanidins, leading to the formation of the proline–proanthocyanidin complex [ 65 ]. Next, in 2021, a report suggested that the biomodification of deep dentin with proanthocyanidins showed the highest shear BS, followed by riboflavin and the control group (no collagen crosslinker modification) [ 157 ]. Proanthocyanidins can be incorporated into the etching solution and experimental primer to enhance the stability of bonding, while proanthocyanidins incorporated into an experimental adhesive showed no negative effect but stabilized the interfacial resin–dentin bonds, confirming the outcome obtained in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Proanthocyanidins can be incorporated into the etching solution and experimental primer to enhance the stability of bonding, while proanthocyanidins incorporated into an experimental adhesive showed no negative effect but stabilized the interfacial resin–dentin bonds, confirming the outcome obtained in this analysis. Other studies showed a drawback of proanthocyanidins in terms of discoloration (a brownish color) of the substrate treated [ 65 , 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dentin biomodification with 6.5% proanthocyanidin was found to have the strongest bond strength in permanent teeth [25,26]. However, when we used the same concentration for treating primary teeth in our study, we did not get the same results.…”
Section: Discussionmentioning
confidence: 56%